2009
DOI: 10.1021/jp806694j
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Self-Selectivity in Two Model Dinitrobenzoyl-Derivatized Brush-Type Chiral Stationary Phases

Abstract: A study of chiral self-discrimination in two model chiral stationary phases, N- (3,5-dinitrobenzoyl-phenylglycine and N-(3,5-dinitrobenzoyl)leucine, is described. "Brush-type" chiral interfaces are obtained by attaching these compounds onto oxidized Si(111) samples and atomic force microscopy tips by using two sample preparation procedures: a direct and a two-step surface deposition of the chiral stationary phase onto the substrate. By using AFM, the morphologies of the resulting chiral interfaces are obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…We have previously reported on the self-selectivity of N -(3,5-dinitrobenzoyl)phenylglycine and N -(3,5-dinitrobenzoyl)leucine CSPs in a series of protic and aprotic solvents. We found that the less sterically hindered and more flexible leucine moiety led to increased hydrogen bonding with the solvent. This interaction with the solvent occurred at the carbonyl and amide groups within the selector and reduced chiral discrimination because the sites were not available for interactions with the analyte.…”
Section: Introductionmentioning
confidence: 96%
“…We have previously reported on the self-selectivity of N -(3,5-dinitrobenzoyl)phenylglycine and N -(3,5-dinitrobenzoyl)leucine CSPs in a series of protic and aprotic solvents. We found that the less sterically hindered and more flexible leucine moiety led to increased hydrogen bonding with the solvent. This interaction with the solvent occurred at the carbonyl and amide groups within the selector and reduced chiral discrimination because the sites were not available for interactions with the analyte.…”
Section: Introductionmentioning
confidence: 96%